Perceived Social Support among Mentally Ill Patients - Pokharel, Bandana; Pokharel, Anupama (Journal of Lumbini Medical College, 2016)
Introduction: Social support is the perception that one is cared for, has assistance available from significant others and its benefit is by buffering stress by influencing the ability to adjust and live with illness. Social support can uplift the quality and subjective wellbeing of people. The objective of this study was to examine the perceived social support and factors influencing it among mentally ill patients.Methods: A descriptive cross-sectional study was carried out. Ninety cases aged more than 18 years visiting outpatient of psychiatric department and diagnosed as a case of mental illness for at least a year were included. Instruments used were self-developed proforma and Multidimensional Scale of Perceived Social Support. Interview technique was used to collect the data.Results: Majority (60%) of the patients perceive social support from family, 28% of the patients perceive social support from significant others. Regression analysis showed that the perceived social support is influenced by employment status, type of family one lives in and physical illness. It is not influenced by gender, subjective financial status and frequency of hospitalization.Conclusion: Perceived social support is influenced by employment status, type of family one lives in and physical illness. Majority (60%) of the patients perceive social support from family.Journal of Lumbini Medical College. 2014;2(1):14-17.